Tax E-filing Adoption in Malaysia: A Conceptual Model - Kamarulzaman, Y.; Che Azmi, A.A. (IBIMA Publishing, 2010)
Tax e-filing is one of the e-government services that is gaining importance for public to perform their responsibility to the country through tax payment. Despite the rapid adoption of e-filing in Malaysia, the e-filing system is still unreliable especially at peak period which lead to high level of risk perceived by taxpayers. This paper proposes a framework that incorporates the significant affect of performance risk, which is a significant perceived risk facet, on tax e-filing adoption in Malaysia. In this paper, the framework also posits the perceived risk and performance risk within the Technology Acceptance Model (TAM) within the e-filing context. This model will serve as a useful guideline not only for devising strategies to promote e-government services, particularly tax e-filing service but also to improve the performance of the e-filing system.